2015
DOI: 10.1155/2015/619560
|View full text |Cite
|
Sign up to set email alerts
|

Dandelion Extracts Protect Human Skin Fibroblasts from UVB Damage and Cellular Senescence

Abstract: Ultraviolet (UV) irradiation causes damage in skin by generating excessive reactive oxygen species (ROS) and induction of matrix metalloproteinases (MMPs), leading to skin photoageing. Dandelion extracts have long been used for traditional Chinese medicine and native American medicine to treat cancers, hepatitis, and digestive diseases; however, less is known on the effects of dandelion extracts in skin photoageing. Here we found that dandelion leaf and flower extracts significantly protect UVB irradiation-inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 23 publications
(56 reference statements)
0
36
0
2
Order By: Relevance
“…Various herbal extracts have shown beneficial properties as indicated in some studies. [2125] We examined A. vera , henna, A. capillus-veneris and C. molmol extracts and their mixture for treatment of normal mouse skin fibroblast line. It was demonstrated that methanolic extract of A. capillus-veneris and C. molmol and ethanolic extract of hennasignificantly improved the expression of Tgfβ1 and Vegf-A genes at 48 h after treatment of fibroblast cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various herbal extracts have shown beneficial properties as indicated in some studies. [2125] We examined A. vera , henna, A. capillus-veneris and C. molmol extracts and their mixture for treatment of normal mouse skin fibroblast line. It was demonstrated that methanolic extract of A. capillus-veneris and C. molmol and ethanolic extract of hennasignificantly improved the expression of Tgfβ1 and Vegf-A genes at 48 h after treatment of fibroblast cells.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, intracellular formazan can be solubilized and distinguished by spectrophotometric means. [2526]…”
Section: Methodsmentioning
confidence: 99%
“…Dermal fibroblasts, which mainly comprise the dermis layer of the skin, are established to contribute to the generation of connective tissues4243. During skin aging, MMPs, which are generated from dermal fibroblasts, can degrade all components in the ECM, including collagen, elastin, laminin, and proteoglycans44.…”
Section: Discussionmentioning
confidence: 99%
“…Водные экстракты листьев, цветов и корней одуванчика (Taraxacum officinale) тормозили стресс-индуцированное старение фибробластов кожи человека, вызванного перекисью водорода, на 62%, 73% и 40%, соответственно. При этом защитное действие экстракта одуванчика не зависело от того, был ли он добавлен до или после Н 2 О 2 [24]. Используемый в китайской медицине водный экстракт шести растений (Kangen-karyu) защищал фибробласты от стресс-индуцированного старения, как в условиях преинкубации, так и при добавлении после Н 2 О 2 .…”
Section: результаты и обсуждениеunclassified